PERBEDAAN PERILAKU BERBELANJA ANTARA WANITA KARIR DAN IBU RUMAH TANGGA PADA PASAR SWALAYAN RAMAYANA BOGOR - Achjadi Mustafa (Jurnal Ilmiah Binaniaga, 2006)
Descriptive statistics analysis was applied in this research, and the method concerns to evaluate shopping behavior only, base on seven of Zeithaml’s dimentions. Statistic analysis uses t-test to evaluate the behavior difference between women who work outdoor and housewives. Total samples taken for this study are 99 housewives and 97 women who work outdoor. These samples are part of population with 12.320 housewives and 3.680 women employed to pick samples for their population, researcher uses slovin method. The gain of research shows us that there are not significant differences between wpman employed and housewives in shopping behavior. Results get t-value = 2,017 which less than ttable = 2,178.